Prevalence of Asymptomatic Bacteriuria among Pregnant Women At Damietta Governorate, Egypt - Eman Abd EL- Aziz (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background:Asymptomatic bacteriuria during pregnancy is a main health problem, which is related to an increased risk of    maternal and fetal morbidity. Aim of the Work:To estimate incidence of asymptomatic bacteriuria among pregnant females at Damietta Governorate, Egypt. Patients and Methods:Five hundred randomly selected pregnant females attending antenatal care units at Damietta Governorate during the period July, first, 2019 – January 31st, 2021. All participants were subjected to full history taking, complete blood count as well as urine culture and bacterial count. Result:A relatively high incidence of asymptomatic bacteriuria [13.8%] was revealed among participants in whom the most causative organism was Escherichia coli. The rate was lower among pregnant women with a high social standard and during the first trimester. Maternal age, parity, education level, or hemoglobin level, on the other hand, had no significant relationship . Conclusion: Screening of asymptomatic bacteriuria in pregnancy must be added to routinely antenatal care investigations and doing another studies on a wider scope are recommended.